2016
DOI: 10.1007/s12010-016-2039-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Altitudes and Habitats on Valerenic Acid, Total Phenolics, Flavonoids, Tannins, and Antioxidant Activity of Valeriana jatamansi

Abstract: The changes in total phenolics, flavonoids, tannins, valerenic acid, and antioxidant activity were assessed in 25 populations of Valeriana jatamansi sampled from 1200 to 2775 m asl and four habitat types of Uttarakhand, West Himalaya. Significant (p< 0.05) variations in total phenolics, flavonoids, valerenic acid, and antioxidant activity in aerial and root portions and across the populations were observed. Antioxidant activity measured by three in vitro antioxidant assays, i.e., 2,2'-azino-bis(3-ethylbenzothi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 38 publications
0
35
1
Order By: Relevance
“…For example, Kalim, Bhattacharya, Banerjee, and Chattopadhyay () analyzed the antioxidant activity in the root extracts of V. jatamansi using different assays (DPPH free radical scavenging, hydroxyl radical [OH] scavenging, peroxynitrite scavenging activity, nonenzymatic superoxide radical scavenging activity, and nitric oxide scavenging activity) demonstrated that the species possess enormous antioxidant activity (IC 50 values for scavenging DPPH: 86.61; ABTS: 21.26; OH: 37.92, O 2 :78.35; and ONOO − : 943.12 μg/ml). Likewise, antioxidant activity of essential oil and methanol extracts (Thusoo et al, ), essential oil and supercritical CO 2 fluid extracts (Pandian & Nagarajan, ), and aerial and root portions extract of V. jatamansi were also reported (Jugran et al, ). Bhatt et al () evaluated the antioxidant potential of extract and essential oil of wild and planted individuals of V. jatamansi using different in vitro methods and observed that root samples from planted individuals possess significantly higher ( p < 0.05) antioxidant activity (ABTS: 4.87 mg/g; FRAP: 10.18 mg/g ascorbic acid equivalent dry weight).…”
Section: Medicinal Uses and Pharmacology Propertiesmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, Kalim, Bhattacharya, Banerjee, and Chattopadhyay () analyzed the antioxidant activity in the root extracts of V. jatamansi using different assays (DPPH free radical scavenging, hydroxyl radical [OH] scavenging, peroxynitrite scavenging activity, nonenzymatic superoxide radical scavenging activity, and nitric oxide scavenging activity) demonstrated that the species possess enormous antioxidant activity (IC 50 values for scavenging DPPH: 86.61; ABTS: 21.26; OH: 37.92, O 2 :78.35; and ONOO − : 943.12 μg/ml). Likewise, antioxidant activity of essential oil and methanol extracts (Thusoo et al, ), essential oil and supercritical CO 2 fluid extracts (Pandian & Nagarajan, ), and aerial and root portions extract of V. jatamansi were also reported (Jugran et al, ). Bhatt et al () evaluated the antioxidant potential of extract and essential oil of wild and planted individuals of V. jatamansi using different in vitro methods and observed that root samples from planted individuals possess significantly higher ( p < 0.05) antioxidant activity (ABTS: 4.87 mg/g; FRAP: 10.18 mg/g ascorbic acid equivalent dry weight).…”
Section: Medicinal Uses and Pharmacology Propertiesmentioning
confidence: 94%
“…12.8 | Anti-inflammatory activity Khuda, Iqbal, Khan, Zakiullah, and Shah (2013) (Thusoo et al, 2014), essential oil and supercritical CO 2 fluid extracts (Pandian & Nagarajan, 2015), and aerial and root portions extract of V. jatamansi were also reported (Jugran et al, 2016). (Rawat et al, 2017).…”
Section: Antidepressant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of valtrate was confirmed in the TL chromatogram of the extract. Thus, the antianxiety and antidepressant activity of V. pyrolaefolia is attributable to the presence of valtrate as it is reported to be the anxiolytic principle of other species of valerian [14][15][16][17] .…”
Section: Antidepressant Activitymentioning
confidence: 97%
“…Value of each parameter in populations was classified into five equal classes and a class with higher values was used for prioritization of promising class of population for chemical constituents and antioxidant activity. The classification was performed following method described by Jugran et al 2016. Briefly, the maximum value (a) of each parameter (phytochemical or antioxidant activity) was subtracted from its minimum value (b) and the obtained value (c 5 a 2 b) was divided by 5 (d 5 c/5).…”
Section: Prioritization and Elite Identificationmentioning
confidence: 99%